Short- and Long-Term Effects of Passive and Active Screen Time on Young Children’s Phonological Memory - Veraksa, Nikolay; Veraksa, Aleksander; Gavrilova, Margarita; Bukhalenkova, Daria; Oshchepkova, Ekaterina; Chursina, Apollinaria (Frontiers in Education, 2021)
The purpose of this study was to fill this gap by examining the relationship between phonological memory in preschool children and their passive (watching TV) and active screen time with using of Smart Screen Technologies such as tablets and phones with a touch screen interface. Study was conducted in two stages: in Time 1, the association between children’s phonological memory, passive and active screen time and family factors was examined; in Time 2 (1 year later) the impact of passive and active screen time on a child’s individual progress in phonological memory development was evaluated. The study enrolled 122 preschool children aged 5–6 years (M = 5.72, SD = 0.33); boys (54.9%). Information on each child’s average daily passive and active screen time was obtained from a survey with the mother. The survey provided information on how much time each child spent on a typical day with passive (“traditional”) and active (interactive) use of digital devices. For family factors, we included maternal highest educational qualification, family’s financial situation. For children’s characteristics, age, gender and non-verbal fluid intelligence were included. The results indicate that time spent passively with digital devices (watching TV) is negatively related to a child’s ability to process verbal information. In contrast, the interactive time the child spent with Smart Screen Technologies is not significant and does not pose a threat to the development of phonological memory in preschool age. The study also showed that passive and active use of digital devices has no long-term impact on children’s phonological memory development progress over a year. The implications are that use of Smart Screen Technologies, which implies a higher degree of interactivity, is not associated with either short- or long-term negative effects on phonological memory development in preschool age, contrary to passive screen time exposure. The results can be applied in the elaboration of principles and programs on the use of digital devices for the entertainment and education of preschool children.